Originally Posted by

**Meggomumsie** Hi, I'm really pleased to say that I have learned lots from your answers, thank you again. I do not understand why the last step is taken in the question below. (Change the subject of the formula to y)

$\displaystyle x-2y=10$

$\displaystyle x-10=2y$

$\displaystyle 2y=x-10$

$\displaystyle y=\frac{x-10}{2}$

$\displaystyle y=\frac{x-5}{2}$

I understand that they must have used the common denominator. I thought when you divide one part by the common denominator, you had to divide the other part also, so how do they know that 2 will go into x?

Marilyn